2017
DOI: 10.1001/jamaoncol.2017.1350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cancer at Baseline Screening in the National Cancer Institute Li-Fraumeni Syndrome Cohort

Abstract: This study describes the establishment and feasibility of an intensive cancer surveillance protocol for individuals with Li-Fraumeni syndrome. Prevalent cancers were detected at an early stage with baseline whole-body, brain, and breast MRI. Prospective screening of the participants is under way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…This result supports the relevance of annual examinations for LFS patients. These results are also consistent with previous observations that WB-MRI facilitates the early detection of malignant tumors [ 19 , 26 28 ]. Low positivity and recall rates were observed, and further investigations of positive results predominantly involved radiological methods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result supports the relevance of annual examinations for LFS patients. These results are also consistent with previous observations that WB-MRI facilitates the early detection of malignant tumors [ 19 , 26 28 ]. Low positivity and recall rates were observed, and further investigations of positive results predominantly involved radiological methods.…”
Section: Discussionsupporting
confidence: 93%
“…In 2017, Mai et al [ 28 ] also evaluated a screening protocol that included WB-MRI for examining 116 patients of a National Cancer Institute (NCI) Li-Fraumeni cohort. In this baseline screening, cancers were detected in 6.9% of the cohort, and 34.5% of these lesions required further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative risks of breast and ovarian cancers in BRCA1/2 mutation carriers are reported to be 72% (95% confidence interval [CI], 65 to 79) and 44% (95% CI, 36 to 53), respectively, in BRCA1 carriers and 69% (95% CI, 61 to 77) and 17% (95% CI, 11 to 25), respectively, in BRCA2 carriers [1]. The cumulative cancer risk associated with TP53 mutation may be as high as 90% by the age of 60 years [2]. In addition to mutations in BRCA1/2 and TP53, germline mutations in certain genes were associated with more than 50 hereditary cancer syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…If cancer surveillance does indeed detect a greater frequency of tumors that are treated as compared with what would normally be treated (i.e., unrecognized overdiagnosis of nonmalignant lesions leading to possible overtreatment), this could render the strategy less cost‐effective. However, recent analyses among patients with LFS have found that overdiagnosis and unnecessary treatment of indolent lesions to be uncommon . Additional estimates of tumor development and patient survival using real‐world data are needed to determine the likelihood of this occurring.…”
Section: Discussionmentioning
confidence: 99%